The use of silver hydrogel in wound treatment as an alternative to reduce antibiotic-resistant pathogens (Research, Society and Development, 2022)
Medical science is currently at an early stage for effectively controlling skin damage. One of the main barriers to good wound healing is bacterial infection, which poses a risk of long-term harmful effects. A clean wound, free of bacterial infections, is essential for the quick and effective regeneration of the skin. Hydrogel is one of the best biomaterials for antibiotic delivery in wound areas due to its high hydrophilicity, distinctive three-dimensional network, good biocompatibility, and cell adherence. Although many antibiotics are successful in treating infected wounds, improper or repetitive use of these medications may cause germs to become resistant. Notoriously, antimicrobial resistance in pathogenic bacteria is already considered a serious global public health issue. Recently, the use of silver associated with nanotechnology has been reconsidered as an important alternative to reduce the spread of antibiotic-resistant pathogens. Silver hydrogel dressings have become effective agents in wound management, substituting the use of antibiotics. The objective of this review is to show the importance of hydrogels in wound treatments, as well as the antibacterial properties of silver hydrogels and their implications in wound care.